2015
DOI: 10.1016/j.lfs.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of estrogen, raloxifene and tamoxifen on endothelial dysfunction, inflammatory markers and oxidative stress in ovariectomized rats

Abstract: Raloxifene and tamoxifen have similar anti-inflammatory effects that may be important in improving vascular dysfunction. Tamoxifen did not affect the ROS but improved endothelial dysfunction. The protective effect on endothelial function by these treatments provides evidence of their potential cardiovascular benefits in the postmenopausal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 66 publications
2
22
0
2
Order By: Relevance
“…The experimental model of hormone replacement therapy, associated with surgically-induced anoestrus through bilateral ovariectomy in female rats, is wellknown [16,28,31]. In accordance with the validated animal model, the histopathological analysis in group 2 found evident atrophy in the epithelium, chorion and glandular tissues of the vagina and vulva.…”
Section: Discussionmentioning
confidence: 78%
“…The experimental model of hormone replacement therapy, associated with surgically-induced anoestrus through bilateral ovariectomy in female rats, is wellknown [16,28,31]. In accordance with the validated animal model, the histopathological analysis in group 2 found evident atrophy in the epithelium, chorion and glandular tissues of the vagina and vulva.…”
Section: Discussionmentioning
confidence: 78%
“…RAL has certain effects on cardiovascular diseases, and previous studies revealed that RAL and other SERMs improve the function of vascular endothelial cells [19, 20], dilate the coronary artery [8, 21], and regulate blood fat [22]. However, only a few reports on basic and clinical studies of the effect of RAL on valvular heart disease have been published [23].…”
Section: Discussionmentioning
confidence: 99%
“…Postmenopausal depletion of endogenous estrogens may contribute to tissue injury and apoptosis via induced oxidative stress (Dilek et al 2010;Lamas et al 2015). It has been shown that a reduction in 17β-estradiol (E2) leads to an increase in oxidative stress in the body, which is dependent on the concentration and chemical structure of this hormone (Moreira et al 2007;Dilek et al 2010;Moreira et al 2011).…”
Section: Introductionmentioning
confidence: 99%